Effects of Rimbaka Forest Harvesting Technique on Stream Water Quality and Soil Physical Properties - Deris, Othman (2009)
Forest harvesting has raised public attention and has been blamed for environmental problems especially land slide, soil erosion, flooding and degradation of water quality. In Peninsular Malaysia, forest harvesting in the hill forest mainly uses ground based system with the combination of crawler tractors and winch. In an attempt to reduce soil disturbance and degradation of river water quality, Rimbaka Timber Harvester (RIMBAKA) was introduced as an alternative to the crawler tractor. This study focused on the effects of forest harvesting using RIMBAKA technique on river water quality index and soil physical characteristics. The study was carried out at Hutan Simpan Gunung Benom, Raub, Pahang. This study is important to determine the effects of using RIMBAKA for forest harvesting as it can be considered as an alternative to the ground- based system which has been proven to result in negative impact on soil properties such as soil compaction, increased run-off and erosion and also caused degradation of river water quality. The main objective of this study is to determine the forest harvesting effects on river water quality index and soil physical properties such as texture, bulk density, particle density, porosity and moisture content. Sampling of river water quality and soil physical characteristics were carried out in the area that has been approved for logging at three stages namely before, during and after forest harvesting. In order to determine forest harvesting effects on water quality index, water samples were collected from the stream channel site that flows through the forest harvesting area, logging road and virgin forest area. In addition, river water quality index was also studied during the dry and wet seasons for each site and also forest harvesting phases. The soil was sampled randomly in the area approved for logging during each harvesting phase. Analysis of Variance (ANOVA) was used to detect significant differences in river water quality index and soil physical characteristics for each forest harvesting phase. Duncan Multiple Range Test (DMRT) was used to determine differences between each phase. In order to determine significant differences between river water quality during dry and wet seasons, a T-test was conducted. Meanwhile, Pearson’s correlation coefficient was used to determine the turbidity and TSS relationship. T-test was also used to determine differences between soil physical characteristics at two altitudes (below and above 550 meters above sea level (masl)). It was found that RIMBAKA harvesting technique has adversely affected to water quality index. Water quality slightly decreased during the wet season as compared to the dry season. The decline in water quality index is caused by an increase in Total Suspended Solid (TSS). During wet seasons, TSS value before, during and after forest harvesting were 13.38 mg/L, 52.67 mg/L and 66.00 mg/L, respectively. The corresponding values during dry seasons were 7.58 mg/L, 33.08 mg/L and 27.83 mg/L, respectively.Stream crossing during road construction is the main factor in that increase TSS concentration. During the harvesting phase in the wet season, TSS value in the stream water at the road crossing is 71.07 mg/L compared to 34.5 mg/L at the forest harvesting site and 28.83 mg/L at the control area. Meanwhile, after forest harvesting, TSS value at the forest road site, harvesting area and the control area are 88.75, 43.25 and 33.0 mg/L, respectively. However, an increase in TSS value only resulted in a slight effect on water quality index value. Water quality index before, during and after forest harvesting belong to Class I and II. Turbidity and suspended solids showed strong linear relationship (r2 = 0.769). The forest harvesting operation also changed the texture, increased the bulk density and soil particle density. Indirectly, the changes had caused a decline in the porosity and soil moisture (P≤0.05). Based on this study, forest harvesting using RIMBAKA technique only resulted in slight negative effects on water quality index and soil physical characteristics. However, the negatives effects can be further reduced if the forest harvesting is confined to dry season only. It is recommended that in future studies, more sampling should be carried out in the logging area to provide a more complete picture of the changes in soil and river water quality.